Attitudes of University Students towards Abortion in Nigeria: The Role of Health Counselling - Olaitan, Olukunmi Lanre; Oniye, Abdulrazaq; Olawuyi, Bolanle; Bakinde, Surajudeen; Aina, Michael (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
The study examined the attitude of university students towards abortion in Nigeria. A total of nine hundred (900) respondents gave their opinions on a self-structured questionnaire. The frequency counts and percentages were used to analyse the personal data of the respondents and means, standard deviation, t-test and analysis of variance (ANOVA) for analyzing the hypotheses at Î±=0.05 level of significant. Some students support abortion when it is on health condition of either the mother or the baby. Based on the findings, some of the recommendations made include proper reproductive health education and health counseling should be given to young ladies and boys about unsafe abortion preventive method, Federal Government as a matter of urgency should consider legalization of induced abortion to prevent the practice of clandestine abortion in the back street.   Keywords: Attitudes, University, Students, Abortion, Health Counselling, Nigeria